2001
DOI: 10.1073/pnas.201400998
|View full text |Cite
|
Sign up to set email alerts
|

Speech comprehension is correlated with temporal response patterns recorded from auditory cortex

Abstract: Speech comprehension depends on the integrity of both the spectral content and temporal envelope of the speech signal. Although neural processing underlying spectral analysis has been intensively studied, less is known about the processing of temporal information. Most of speech information conveyed by the temporal envelope is confined to frequencies below 16 Hz, frequencies that roughly match spontaneous and evoked modulation rates of primary auditory cortex neurons. To test the importance of cortical modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
490
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 487 publications
(547 citation statements)
references
References 54 publications
52
490
3
2
Order By: Relevance
“…Representation of the temporal stimulus envelope in the cortical activity was quantified in the time domain using cross-correlation analysis (Ahissar et al 2001;Abrams et al 2008;Nourski et al 2009). Envelopes of the speech stimuli were obtained by calculating the magnitude of the Hilbert transform of the speech signal waveform and low-pass filtering at 50 Hz using a fourth-order Butterworth filter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Representation of the temporal stimulus envelope in the cortical activity was quantified in the time domain using cross-correlation analysis (Ahissar et al 2001;Abrams et al 2008;Nourski et al 2009). Envelopes of the speech stimuli were obtained by calculating the magnitude of the Hilbert transform of the speech signal waveform and low-pass filtering at 50 Hz using a fourth-order Butterworth filter.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in normalhearing listeners have demonstrated that time compression of speech led to decreases in intelligibility and in phase locking of the auditory cortical responses to the temporal envelopes of these sentences (Ahissar et al 2001;Ahissar and Ahissar 2005). Our previous studies have used these stimuli to establish that time locking to the speech temporal envelope could be present in core auditory cortex even when speech was severely time-compressed and, as a result, incomprehensible (compression ratio 0.20).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Procedure to generate simulated maps of coherence with a reference signal Our simulations of coherence with a reference signal were designed to tightly match real brain-speech entrainment data in which MEG signals from auditory regions of a listener are coherent with the temporal envelope of heard speech at~0.5 Hz and 4-8 Hz (Ahissar et al, 2001;Bourguignon et al, 2013a;Luo and Poeppel, 2007;Molinaro et al, 2016;Peelle et al, 2013;Vander Ghinst et al, 2016). Accordingly, we simulated coherence at 0.5 Hz between MEG data and a fixed reference signal taken as the speech envelope of a 5-min audio recording of a person reading a continuous text.…”
Section: Simulationsmentioning
confidence: 99%
“…In that method, we use a bootstrap procedure (Efron, 1979) to estimate a sample distribution of coordinates of maxima in the to-be-compared conditions, and we test the null hypothesis that the distance is zero. The sensitivity and specificity of this test are evaluated on simulated data and on real brain-speech entrainment data wherein brain activity is coherent with heard speech in a natural speech listening task (Ahissar et al, 2001;Bourguignon et al, 2013a;Luo and Poeppel, 2007;Molinaro et al, 2016;Peelle et al, 2013;Vander Ghinst et al, 2016).…”
Section: Introductionmentioning
confidence: 99%